Sampling and Evaluating the Peripheral Nervous System. (January 2020) - Butt, Mark T.
Many preclinical investigations limit the evaluation of the peripheral nervous system (PNS) to paraffin-embedded sections/hematoxylin and eosin–stained sections of the sciatic nerve. This limitation ignores several key mechanisms of toxicity and anatomic differences that may interfere with an accurate assessment of test article effects on the neurons/neurites peripheral to the brain and spinal cord. Ganglion neurons may be exposed to higher concentrations of the test article as compared to neurons in the brain or spinal cord due to differences in capillary permeability. Many peripheral neuropathies are length-dependent, meaning distal nerves may show morphological changes before they are evident in the mid-sciatic nerve. Paraffin-embedded nerves are not optimal to assess myelin changes, notably those leading to demyelination. Differentiating between axonal or myelin degeneration may not be possible from the examination of paraffin-embedded sections. A sampling strategy more consistent with known mechanisms of toxicity, atraumatic harvest of tissues, optimized fixation, and the use of resin and paraffin-embedded sections will greatly enhance the pathologist's ability to observe and characterize effects in the PNS.